Pengembangan Helm Pendeteksi Klakson untuk Berkendaraan pada Anak Gangguan Pendengaran - Nursafitri, Desy; Taufan, Johandri (Jurnal Penelitian Pendidikan Khusus, 2021)
This research is motivated by the problems experienced by children with hearing loss. Where children have problems in driving mobility, children have feelings of anxiety and fear when they want to drive because of the obstacles the child has. Here, researchers develop a tool that can detect horn sounds that can help children when they are driving. In this study, researchers used research and development of a horn detector helmet (HEPEKSON). The purpose of this development is for children to feel safe and not anxious in driving mobility. This Hepekson development research uses the R&D method, Bord and Gall's development theory which has 10 steps of development research, but the researchers limit these steps to five steps, namely reassess and information, planning, develop primary from a product, preliminary field testing and main. product revisions. The results of this development research for the practical aspect an average score of 28.5 the usability aspect an average score of 3 and the feasibility aspect an average score of 3. So from the validation results, the tool is suitable for use by children with hearing loss in detecting horn sounds. while driving